The Wellmark and University of Iowa Partnership: An Innovative Model for Collaboration between Blue Cross-Blue Shield Plans and Colleges - Lawrence Prybil; Mary Charlton; Peter Roberts (SAGE Publishing, 2006)
Wellmark Blue Cross-Blue Shield and the University of Iowa College of Public Health share a strong commitment to improving the health of communities they serve in Iowa and South Dakota. Beginning in 2002, these organizations forged an innovative partnership through which they annually select several collaborative projects that are congruent with their respective missions and address clearly defined needs. The outcomes of their joint efforts toward the partnership's goals are formally assessed on an annual basis. This cooperative arrangement has proven to be workable and beneficial, and may have applications in other settings.